Overall Grading of Plantations and Setting Weightage based on Priority of Parameters - Panda, Arunangsu (Indian Forester, 2019)
Various State Governments monitor the plantations raised by them periodically and collect data regarding location, extent, survival percentage, average height, girth etc. In this paper, efforts were made to prioritise these parameters and integrate them to get an overall grading of plantation so that various plantations within schemes and between schemes can be compared and ranked properly. In future this grading can be related with sustainablility so that management can take remedial measures in plantations with low grades.